Standing Commitment of Sale and Purchase Agreement (PPJB) in Purchasing Flats Unit as Legal Protection for Consumers - Ni Putu Teresa Giovana (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
Research on the commitment of binding sale and purchase (PPJB) in terms of the marketing of flats is a step in legal protection for consumers who will buy flats. This PPJB will bind both parties, namely sellers and buyers for the legal sale and purchase. However, often in terms of the marketing of flats, some rogue developers market flats when the apartment building does not yet have a building permit. This is very contrary to Law Number 20 of 2011 concerning Flats, which says that the marketing of flats must be carried out if the apartment has an IMB. This causes uncertainty of protection for consumers in terms of purchasing flats. Plus PPJB is generally made only with a standard agreement made unilaterally so that consumers cannot freely express their opinions, besides that consumers are also susceptible to losses due to PPJB made without the said IMB. This research was conducted to examine the PPJB in terms of protection for consumers of the flats. This research is normative, namely by way of implementing a legal and conceptual approach. The legal material of this study uses primary legal materials, secondary legal materials and tertiary legal materials by conducting legal material collection using a single method, namely literature study. Protection for consumers is done by using PPJB made by a Notary to minimize the impact that might occur in the future.